Integrating Next-Generation Dendritic Cell Vaccines into the Current Cancer Immunotherapy Landscape. Issue 8 (August 2017) - Garg, Abhishek D.; Coulie, Pierre G.; Van den Eynde, Benoit J.; Agostinis, Patrizia
Abstract : Cancer immunotherapy is experiencing a renaissance spearheaded by immune checkpoint inhibitors (ICIs). This has spurred interest in 'upgrading' existing immunotherapies that previously experienced only sporadic success, such as dendritic cells (DCs) vaccines. In this review, we discuss the major molecular, immunological, and clinical determinants of existing first- and second-generation DC vaccines. We also outline the future trends for next-generation DC vaccines and describe their major hallmarks and prerequisites necessary for high anticancer efficacy. In addition, using existing data we compare DC vaccines with ICIs targeting CTLA4, PD1, and PD-L1, and argue that in various contexts next-generation DC vaccines are ready to meet some challenges currently confronting ICIs, thereby raising the need to integrate DC vaccines in future combinatorial immunotherapy regimens. Trends: The field of cancer immunotherapy is experiencing a renaissance spearheaded by ICIs and ACTs. Applicability of ICIs/ACTs is restricted to only a subset of patients, due to limiting factors such as low tumoral T-cell infiltrates, low neoantigens burden, immunoresistant phenotypes, and autoimmune toxicities. These limitations have spurred interest in 'upgrading' existing immunotherapies such as DC vaccines to meet current challenges. Promising clinical ORRs and safety profile of current (second-generation) DC vaccines have raised interest in producing next-generation DC vaccines. Next-generation DC vaccines currently aim to exploit specific DC subsets, naturally occurring DCs, cancer neoantigens, and/or ICD to improve CD8 + T cells–driven anticancer immunity.